Structural, Electrical, And Optical Properties Of Guar Gum‑based Mg2+ion Conducting Biopolymer Blend Electrolytes - Naveen C; M. Muthuvinayagam; Mohd Ikmar Nizam Mohamad Isa (Springer Science and Business Media LLC (Springer), 2025)
Indexed by WOS/ Scopus